Primary leiomyosarcoma with osteosarcomatous differentiation of the breast - Sethi, Ekta; Misra, Sunayana; Ahuja, Arvind (Autopsy and Case Reports, 2024)
Primary leiomyosarcoma with osteosarcomatous differentiation of the breast is an uncommon entity. We present the case of a 37-year-old female who presented with a lump in the breast and pulmonary lesions on PET-CT, for which she underwent a toilet mastectomy. Histopathological examination revealed a tumor with cells arranged in sheets. These tumor cells had moderate eosinophilic cytoplasm, highly pleomorphic, irregular hyperchromatic nuclei, coarse chromatin, and prominent nucleoli. Areas with spindle-cell morphology were noted. Osteoid was seen intermingling with the tumor along with numerous osteoclast-like multinucleate giant cells. A wide panel of Immunohistochemistry was applied, and Desmin, h-Caldesmon, SMA, and Vimentin were positive. The patient died 3 months post-surgery and had a recurrence at the surgical site.